Uninterruptible Power Supply (UPS) using high frequency transformer [electronic resource] - Suzana Pil Ramli, 1981- (2010)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2010